Liutex and its applications in turbulence research - Liu, Chaoqun; Xu, Hongyi; Cai, Xiaoshu; Gao, Yisheng (Academic Press, 2021)
Liutex and Its Applications in Turbulence Research reviews the history of vortex definition, provides an accurate mathematical definition of vortices, and explains their applications in flow transition, turbulent flow, flow control, and turbulent flow experiments. The book explains the term "Rortex" as a mathematically defined rigid rotation of fluids or vortex, which could help solve many longstanding problems in turbulence research. The accurate mathematical definition of the vortex is important in a range of industrial contexts, including aerospace, turbine machinery, combustion, and electronic cooling systems, so there are many areas of research that can benefit from the innovations described here. This book provides a thorough survey of the latest research in generalized and flow-thermal, unified, law-of-the-wall for wall-bounded turbulence. Important theory and methodologies used for developing these laws are described in detail, including: the classification of the conventional turbulent boundary layer concept based on proper velocity scaling; the methodology for identification of the scales of velocity, temperature, and length needed to establish the law; and the discovery, proof, and strict validations of the laws, with both Reynolds and Prandtl number independency properties using DNS data. The establishment of these statistical laws is important to modern fluid mechanics and heat transfer research, and greatly expands our understanding of wall-bounded turbulence.